The Death of Expertise as Indicated through Donald Barthelme’s The Balloon - Rommel Utungga Pasopati; Cahyaningsih Pujimahanani; Asihta Aulia Azzahra (British : Jurnal Bahasa dan Sastra Inggris, 2022)
Literary criticisms state stable theories, while meanings nowadays push people to interpret out of merely theories. People focus on opinions, assumptions, and common discourses as this is age of The Death of Expertise as supported by Tom Nichols. The Balloon is Donald Barthelme’s short story that tells a balloon that suddenly appears in New York. No one really knows where it comes from or why it exists. Experts and governments are trying to get rid of it but none could do anything. People try to understand that by own understandings since it is open for meanings. This paper would like to indicate death of expertise on The Balloon. Through qualitative method on cultural studies, this paper emphasizes conditions of the balloon, incapability of experts, and responses of common people towards that. Barthelme asserts how everyone has own meanings to understand based on own experience. Theories matter, but more of them are needed to understand aspects of an event. Barthelme tends to show how an event could bring in flexible meanings through experience alongside with rigid definitions through analytical theories. Nichols underlines that experts approach through exact theories, but flexibility could only be found through experience.Keywords: Cultural Studies, Donald Barthelme, The Balloon, The Death of Expertise